Characterization, Compressive Strength and Output Voltage Properties of Silica/Barium Titanate Nanocomposite for Piezoelectric Applications - Hamzah, Muhammad Sadat; Fadly, Muhammad Syaiful; Wildan, Muhammad Waziz; Kusmono; Suharyadi, Edi (Applied Science and Engineering Progress, 2026)
The influence of nano-sized barium titanate addition on the compressive strength and output voltage of silica/barium titanate nanocomposites was investigated. Nano silica powder, synthesized from silica sand via an alkaline fusion method assisted by 200 Hz speaker membrane vibration, was combined with nano barium titanate using the solid-state method at 10, 20, 30, and 40 wt% variations. Samples were uniaxially compacted at 75 MPa and sintered at 1390 °C for 2 hours under atmospheric conditions. The highest bulk density (2.72 g/cm³) and compressive strength (37.01 MPa) were achieved at 10 wt% barium titanates. XRD analysis revealed quartz, tridymite, and cristobalite phases and the emergence of fresnoite (Ba₂TiSi₂O₈) and BaTiSiO₅ phases at higher BT contents. The maximum output voltage (5.51 mV) was obtained at 40 wt% barium titanate, indicating the material’s potential for piezoelectric applications.